Analysis of Traffic Accidents on the Lonjengan-Tanjam Section, Menjalin District, Landak Regency - Inong, Paramitha; Kadarini, S. Nurlaily; Said, Said (Jurnal Teknik Sipil, 2025)
The rapid growth of the population has led to an increase in motor vehicle volume, which contributes to a higher risk of traffic accidents and results in significant social and economic impacts. Therefore, a comprehensive analysis is required to identify accident-prone areas and formulate effective mitigation strategies. This study was conducted along the Jalan Lonjengan"“Tanjam, a national road with a total length of 13 km located in Menjalin Subdistrict, Landak Regency. The methods used include the Accident Equivalent Number (AEK) and the Upper Control Limit (BKA) to identify road segments categorized as accident-prone areas (black sites). Data were obtained through field surveys and traffic accident records from 2021 to 2023 provided by the Menjalin Police Sector Traffic Unit (Satlantas Polsek Menjalin). The road was divided into 13 segments, each 1 km in length. The analysis revealed that Segments 7 to 10 had AEK values exceeding the BKA threshold. The dominant accident characteristics included minor injuries, riders aged 31"“45, and side-impact collisions, which mostly occurred during the afternoon and on Fridays. Recommended measures include the installation of warning signs and delineators and regular maintenance of road markings to enhance traffic safety.